COVID‐19 and housing market effects: Evidence from U.S. shutdown orders. (17th January 2022) - D'Lima, Walter; Lopez, Luis Arturo; Pradhan, Archana
Abstract: This paper provides novel evidence on pricing effects in housing markets following government shutdown responses to COVID‐19 using microlevel data on U.S. residential property transactions. We find that post‐shutdown pricing effects not only depend on population density but also the size and structural density of properties. The average price of a three‐bedroom property fell by approximately 1.4% in densely populated locations (e.g., downtown) but increased by about 1.5% in low‐density locations (e.g., suburbs) where shutdowns were enacted. The effects are more drastic for properties with fewer bedrooms. We also document a significant decrease in sales for markets under a shutdown.